Feline Temporal Lobe Epilepsy: Review of the Experimental Literature. (6th April 2017) - Kitz, S.; Thalhammer, J.G.; Glantschnigg, U.; Wrzosek, M.; Klang, A.; Halasz, P.; Shouse, M.N.; Pakozdy, A.
Abstract : Accumulating evidence suggests that epileptic seizures originating from the temporal lobe (TL) occur in cats. Typically, affected animals have clinically focal seizures with orofacial automatisms including salivation, facial twitching, lip smacking, chewing, licking, and swallowing. Motor arrest and autonomic and behavioral signs also may occur. Many affected cats have magnetic resonance imaging (MRI) changes within the hippocampus or histopathologically confirmed hippocampal sclerosis or necrosis. From the 1950s to the 1980s, cats frequently were used as animal models for neurophysiological experiments and electrophysiological studies, from which important basic knowledge about epilepsy originated, but which has been rarely cited in clinical veterinary studies. These studies were reviewed. Experimental research on cats showed the widespread anatomical connections among TL structures. The ictal clinical signs originating from the hippocampus, amygdala, or lateral temporal cortex are similar, because of their dense interconnections. The ictal signs can be divided into autonomic, somatic, and behavioral. For research purposes, a 6‐stage system was established, reflecting the usual sequential progression from focal to generalized seizure: attention response (1), arrest (2), salivation, licking (3), facial twitching (4), head turning or nodding (5), and generalized clonic convulsions (6). Knowledge of this data may help in recognizing low‐stage (stage 1 or stage 2) epileptic seizures in clinical practice. Early experimental research data are in accordance with recent clinical observations regarding ictal clinical signs of TL epileptic seizures in cats. Furthermore, the research data supports the idea that TL epilepsy represents a unique clinical entity with a specific seizure type and origin in cats.